2022
DOI: 10.1371/journal.pone.0278204
|View full text |Cite
|
Sign up to set email alerts
|

The association of herd performance indicators with dairy cow longevity: An empirical study

Abstract: The associations between reproductive performance, milk yield and health status with the risk of culling, and thus with a cow’s longevity, have been well documented at the individual cow level. Associations at individual cow level may, however, not be valid at herd level due to interrelated herd management aspects and/or policy restrictions. The objective of this study was to explore the association of herd performance indicators with herd-level dairy cow longevity under Dutch production conditions. Longevity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The total replacement rate was comparable to the national culling rate reported by CRV (CRV, 2021b) of 28% in the year 2020-2021 from which most of the inputs were defined. Similarly, several studies, reported an average culling rate of 25% in the Netherlands in the past two decade which was slightly lower than the results of our base scenario (Han et al, 2022;Nor et al, 2014b) From the sensitivity analyses (Table 5.3), it was clear that the base scenario was sensitive to the economic inputs such as milk prices, carcass value and heifer rearing costs but not to the feed costs. This showed that the consequences of changes in market prices could change the optimal policy for replacement regardless of constrained heifer supply, which agreed with the findings of Demeter et al (2011) and, Kalantari et al (2010.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…The total replacement rate was comparable to the national culling rate reported by CRV (CRV, 2021b) of 28% in the year 2020-2021 from which most of the inputs were defined. Similarly, several studies, reported an average culling rate of 25% in the Netherlands in the past two decade which was slightly lower than the results of our base scenario (Han et al, 2022;Nor et al, 2014b) From the sensitivity analyses (Table 5.3), it was clear that the base scenario was sensitive to the economic inputs such as milk prices, carcass value and heifer rearing costs but not to the feed costs. This showed that the consequences of changes in market prices could change the optimal policy for replacement regardless of constrained heifer supply, which agreed with the findings of Demeter et al (2011) and, Kalantari et al (2010.…”
Section: Discussionmentioning
confidence: 48%
“…and farm-specific characteristics (Alvåsen et al, 2012;Han et al, 2022;Nor et al, 2014a) but these associations did not completely explain the variation in culling magnitudes or reasons for culling between different farms. Nor et al (2014) pointed out that the majority of studies on culling reasons focus on the performance of individual cows whereas the farmer's style, culture and individual herd management might play a role in culling decisions as well.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations